Auriculotherapy application in elderly individuals treated in primary health care: a quasi-experimental clinical study (Brazilian Journal of Health Research, 2021)
Introduction: The present study addresses auriculotherapy, which is a technique of traditional Chinese medicine focused on treating several health issues based on neurophysiology and reflexology. Objective: Evaluating the effectiveness of auriculotherapy in managing pain, within 4 weeks, in elderly individuals followed up in primary healthcare services in an inland county in Northeastern Brazil. Methods: Quasi-experimental clinical study carried out from May to June 2018. Evaluation instruments comprised sociodemographic and health questionnaire, Nordic musculoskeletal questionnaire and visual analog scale for pain. Participants were followed-up for 4 weeks, when they were subjected to auriculotherapy. Bivariate analysis was performed based on ANOVA test to compare pre- and post-intervention means. Results: Seventy-one (71) elderly individuals initially participated in the study; their mean age was 68.9 ± 6.6 years, and they were mostly women (90.1%). However, only 40 elderly individuals completed the study. The most prevalent painful regions comprised knees (56.3%), shoulders (52.1%) and lower back (50.7%). The initial mean recorded for pain was 6.43 ± 1.8 and the final one was 3.15 ± 1.6; this outcome showed significantly improved pain (p
Keywords: Auriculotherapy; Elderly; Pain; Primary health care